Networking in Cloud Computing: Embracing Contests and Seizing Prospects - Yasodha K,; M. Shabitha Sree,; Krishna Sri. S,; Kirubha Shakthi. J,; Karthick. K,; Kanishka. N, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Cloud computing presents the concept of utility computing, which allows users to access computing, storage, and networking resources as needed, with a usage-based pricing model. However, consumers have limited control over network resources, and cloud-computing providers confront a number of issues when operating infrastructure as a service (IaaS) environments. This research investigates the networking difficulties and federation challenges inherent in IaaS, as well as unique software-defined networking (SDN) concepts that could provide efficient solutions for future deployments.
Keywords: Infrastructure As A Service; Software-Defined Networking; Cloud Computing